Combining local knowledge and occupancy analysis for a rapid assessment of the forest elephant Loxodonta cyclotis in Cameroon's timber production forests. Issue 1 (19th March 2018) - Brittain, Stephanie; Ngo Bata, Madeleine; De Ornellas, Paul; Milner-Gulland, E. J.; Rowcliffe, Marcus
Abstract: Information on the distribution and abundance of the forest elephant Loxodonta cyclotis is needed to allocate limited resources appropriately and set conservation goals for the species. However, monitoring at large scales in forest habitats is complicated, expensive and time consuming. We investigated the potential of applying interview-based occupancy analysis as a tool for the rapid assessment of the distribution and relative abundance of forest elephants in eastern Cameroon. Using single-season occupancy models, we explored the covariates that affect forest elephant occupancy and detectability, and identified spatial and temporal patterns in population change and occupancy. Quantitative and qualitative socio-demographic data offer additional depth and understanding, placing the occupancy analysis in context and providing valuable information to guide conservation action. Detectability of forest elephants has decreased since 2008, which is consistent with the decline in perceived abundance in occupied sites. Forest elephants occupy areas outside protected areas and outside the known elephant range defined by IUCN. Critical conservation attention is required to assess forest elephant populations and the threats they face in these poorly understood areas. Interview-based occupancy analysis is a reliable and suitable method for a rapid assessment of forest elephant occupancy on a large scale, as a complement to, or the first stage in, a monitoring process.